Mesenchymal stromal cells for Pseudomonas aeruginosa pneumonia: mechanisms, preclinical evidence, and translational barriers - Zhang, Zhuo-ling; Yu, Ze; Shen, Yue-chuan (Frontiers in Microbiology, 2025)
Pseudomonas aeruginosa, as an important pathogenic bacterium in nature, is particularly prone to cause severe pulmonary infections in patients with weakened immune function, which poses a significant threat to the survival and quality of life of patients. In recent years, Mesenchymal stromal Cells (MSCs) have become a hot topic in the antibacterial research due to their superior immunomodulatory ability and tissue repair characteristics. Existing studies have shown that MSCs have significant potential in improving the immune response to pulmonary infections and promoting tissue repair and regeneration. However, although multiple studies have explored the application of MSCs in pulmonary infections, there are still problems such as unclear mechanisms and high difficulty in clinical translation. This article aims to summarize the latest research progress of MSCs in the treatment of Pseudomonas aeruginosa pulmonary infections, analyze their potential mechanisms of action, clinical application situations, and future research directions, and provide references for in-depth clinical and basic research in this field.